Analisis Aspek Materialitas Dalam Pelaporan Keberlanjutan - Fransiskus Eduardus Daromes; Anthony Holly; Michelle Loeferdy (Universitas Warmadewa, 2023)
The purpose of this study is to analyze how materiality manifests in the reports of several companies in Indonesia in 2020. This study uses qualitative methods by using secondary data in the form of documents as data collection. The results of this study indicate that the economic, environmental, and social activities of each company that are disclosed as material in the report differ with different data completions even though they use the same guidelines (GRI Standards) in the preparation of the report.